Exploring the educational opportunity and implementation of CARE among dental students in India - Soni Rajput; Amit Kumar; Manjunath P Puranik; Namita Shanbhag (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Empathy is considered to be backbone of the patient-physician relationship. The consultation and relational empathy (CARE) measure is widely used internationally to measure empathy. However, no validated tool is available to gather patient feedback on dentists' empathy in India. OBJECTIVE: The objective of this study was to explore the reliability and validity of a CARE measure and to assess the factors influencing CARE score and to determine if there was an association between their CARE score and satisfaction of the patient. SETTING AND DESIGN: A cross-sectional study was done in dental colleges. SUBJECTS AND METHODS: A questionnaire study was carried out among 100 patients from 6 dental colleges in Bangalore using validated CARE measure. STATISTICAL ANALYSIS: Internal consistency of items was evaluated by the Cronbach's alpha, and construct validity was assessed by confirmatory factor analysis. Satisfaction was assessed by a question response on 5-point Likert scale. Descriptive and inferential statistics were performed with significance set at 5%. RESULTS: The mean CARE score was 43.80 ± 5.36. Internal reliability was high (Cronbach's alpha: 0.859) and was reduced by the removal of any of 10 items. High corrected item-total correlations ranged from 0.752 to 0.847. Factor analysis showed a single solution with high item loadings (>0.80). Self-perception of overall health (odds ratio [OR] = 3.78), relationship with family (OR = 4.61) and friends (OR = 3.78), and previous dental experience (OR = 16.00) were more likely, whereas dentist-provided treatment (OR = 0.20), number (OR = 0.07) and dental treatment taken (OR = 0.13), presence of anxiety (OR = 0.03), and fear (OR = 0.05) were less likely to have CARE score. The satisfaction of the patient regressed significantly with the relationship with family members (ß = 0.77) and CARE score (ß = 0.21). CONCLUSION: This study confirms the educational opportunity and implementation of CARE in dental students. CARE scores among patients varied depending on personal factors and dental treatment-related factors. The satisfaction of the patient was influenced by the relationship with family members and CARE scores.